Effects of container type and size on thermal processing characteristics and B-vitamin retention of canned cat food - Dainton, Amanda N.; Molnar, Lydia M.; Aldrich, Charles Gregory (Frontiers in Veterinary Science, 2023)
Introduction: Rigid cans were the traditional container for canned cat foods, but semi-rigid trays/tubs and flexible pouches are popular options as well. Despite this, little is published on the effects of canned cat food container characteristics on thermal processing and retention of B-vitamins. Therefore, the objective was to evaluate the effects of container size and type on thermal processing and B-vitamin retention. Materials and methods: Treatments were arranged in a factorial with two container sizes [small (85-99 g) and medium (156-198 g)] and three container types (flexible, semi-rigid, and rigid). A canned cat food formula was prepared, filled, and sealed into containers before retort processing to a heating cycle target lethality of eight minutes. Internal retort and container temperatures were used to calculate accumulated lethality. Thiamin, riboflavin, niacin, pantothenic acid, pyridoxine, biotin, folic acid, cobalamin, and moisture contents were analyzed in pre- and post-retort samples by commercial laboratories. Thermal processing metrics were analyzed (SAS v. 9.4; SAS Institute, Cary, NC) with the fixed effects of container size, container type, and their interaction. Dry matter basis B-vitamin contents were analyzed with container size, container type, processing stage, and all two-way and three-way interactions as fixed effects. Means were separated using Fisher’s LSD at a P value less than 0.05. Results and discussion: Total accumulated lethality accumulated was greater (P < 0.05) for semi-rigid and flexible containers (average 14.99 minutes) than for rigid containers (12.86 minutes). The greater processing of semi-rigid and flexible containers was likely influenced by required retort settings. Thiamin and riboflavin contents decreased (P < 0.05) by 30.4% and 18.3%, respectively, due to retort processing. Niacin, biotin, and cobalamin were not affected (P > 0.05) by processing. Processing increased (P < 0.05) pantothenic acid (9.1%), pyridoxine (22.6%), and folic acid (22.6%). This was likely caused by sampling or analytical variation. No interaction involving processing stage was significant for any B-vitamin (P > 0.05). B-vitamin retention was not influenced by differences in thermal processing caused by the packaging treatments. Thiamin and riboflavin were the only B-vitamins meaningfully impacted by processing and retention was no improved by any container characteristic.